Youth-centered maternity care: a binational qualitative comparison of the experiences and perspectives of Latina adolescents and healthcare providers - Martha J. Decker; Noelle Pineda; Abigail Gutmann-Gonzalez; Claire D. Brindis (BMC, 2021)
Abstract Background Although there is growing recognition of the importance of person-centered maternity care, the needs and perspectives of pregnant adolescents are rarely considered. The purpose of this study was to compare the maternity care experiences of Mexican-origin adolescents in Guanajuato, Mexico and Fresno, California from both youth and healthcare provider perspectives. Methods Qualitative interviews and focus groups were conducted with a total of 89 respondents, including 74 pregnant and parenting adolescents as well as 15 providers between December 2016 and July 2017. Adolescents also completed a short demographic survey prior to participation. Transcripts in English and Spanish were coded and thematically analyzed using Dedoose software. Results were compared by location and between youth and providers. Results Four themes emerged regarding patient-provider interactions: the need for communication and clear explanations, respectful versus judgmental providers, engaging youth in decision-making, and a focus on the age of the youth and their partners. While youth had similar perspectives and priorities in both locations, youth in Mexico reported more negative healthcare experiences than youth in California. Perspectives varied between the youth and providers, with providers in both California and Mexico identifying several structural challenges in providing quality care to adolescents. In California, challenges to supporting immigrant Latina adolescents and their families included language and translation issues as well as barriers to care due to immigration status and documentation. In both locations, providers also mentioned high patient caseloads and their own concerns about the youth's life choices. Conclusion Youth-centered care requires more effective and respectful patient-provider communication, where adolescents are engaged in their healthcare decision-making and delivery options. Changes in patient-provider interactions can help improve the maternity care experiences and outcomes of Latina adolescents. Healthcare systems and providers need to reconfigure their approaches to focus on the needs and priorities of adolescents.